Pengaruh Penggunaan Media Chatgpt dalam Meningkatkan Motivasi Belajar Ekonomi Siswa Kelas XI SMA Negeri 18 Medan - Titin Sianturi, Putri; Siar Meiriza, Mica (Universitas Batanghari Jambi, 2025)
This study aims to determine the effect of using ChatGPT media on the learning motivation of class XI students of SMA Negeri 18 Medan in the subject of Economics. The background of this study is the low learning motivation of students due to the use of monotonous learning media and the lack of exploration of technology in the learning process. ChatGPT, as an artificial intelligence-based media, is considered capable of providing a more interactive and interesting learning experience. This study uses a quantitative method with a one-shot case study design, where one group of students is given treatment using ChatGPT without a comparison group. The instruments used are questionnaires and observations, with data analysis using normality, homogeneity, and product moment correlation tests through SPSS version 26. The results of the study showed that there was a positive and significant relationship between the use of ChatGPT and learning motivation with a correlation coefficient value of r = 0.728 and an influence contribution of 51.84%. These findings indicate that ChatGPT is an effective learning media in increasing student learning motivation. Therefore, the use of ChatGPT is recommended to be integrated educationally in the learning process in order to create a more active, independent, and interesting learning atmosphere.